First description of a patient with Vici syndrome due to a mutation affecting the penultimate exon of EPG5 and review of the literature†. Issue 12 (20th October 2014) - Ehmke, Nadja; Parvaneh, Nima; Krawitz, Peter; Ashrafi, Mahmoud‐Reza; Karimi, Parviz; Mehdizadeh, Mehrzad; Krüger, Ulrike; Hecht, Jochen; Mundlos, Stefan; Robinson, Peter N.
<x xml:space="preserve">Abstract</x> Vici syndrome is a rare autosomal recessively inherited multisystem disorder characterized by agenesis of the corpus callosum, cataracts, cardiomyopathy, combined immunodeficiency, psychomotor delay, and hypopigmentation. Cullup et al. recently identified mutations in the gene EPG5 as the cause of Vici syndrome. EPG5 is involved in autophagy, an evolutionarily conserved lysosomal degradation process that is essential for cell homeostasis. Following the first description in 1988 by Vici et al., 24 other cases of Vici syndrome have been published with variable expression of the defining features. Here, we report on a further case of Vici syndrome with a homozygous truncating mutation of EPG5, identified by whole‐exome sequencing. The mutation in our patient is the first reported affecting the penultimate exon of EPG5 and presenting with typical clinical manifestations of Vici syndrome. Additionally, we present a detailed clinical analysis of Vici syndrome comprising all cases previously described in the literature. © 2014 Wiley Periodicals, Inc.